(untitled) (Research, Society and Development, 2022)
Objectives: To identify the psychosocial impact generated by the pandemic context of COVID-19 on caregivers and health professionals of a long-stay institution for the elderly, and to analyze pandemic coping strategies. Methods: Observational and cross-sectional study. Ethics committee approval CAAE: 37255020.7.0000.5437. It was carried out between October and November 2020, with application of questionnaires to caregivers and health professionals of “Casa Transitória André Luiz” institution, in Barretos, São Paulo State. The following questionnaires were applied: general (sociodemographic, occupational and testing for COVID-19), the Self-Reporting Questionnaire (SRQ-20), to screen for common mental disorders (CMD), and the Brief-COPE, to list strategies adopted by health workers in coping with the pandemic. Results: From the 57 health workers included in the study, 86.0% are female, 63.2% have completed high school/technical education, 61.4% work less than 40 hours per week and 40.0% reported having tested positive for COVID-19. Considering a score greater than or equal to 7 on the SRQ-20, the probability of occurrence of CMD was screened in 35.1% of the health workers, which was not associated with sociodemographic, occupational variables and testing positive for COVID-19. The most used coping strategies were those related to religion, acceptance, planning/active coping and positive reframing. Health workers with a high probability of CMD had higher median scores in instrumental support and venting than those with a low probability of CMD. Conclusion: A probable occurrence of CMD was identified among the institution’s health workers. This was associated with the search for instrumental support and venting as coping strategies in the pandemic context.